Cdk1-mediated DIAPH1 phosphorylation maintains metaphase cortical tension and inactivates the spindle assembly checkpoint at anaphase - Koutarou Nishimura (Nature Portfolio, 2019)
Cell rounding at mitosis is driven by cortical tension and maintained through metaphase, although the mechanism is unknown. Here, the authors demonstrate that Cdk1 phosphorylation of DIAPH1 is required for both cortical tension maintenance and inactivation of the spindle assembly checkpoint.